Brazil Low Carbon Case Study : Transport - World Bank (Washington, DC, 2013)
This report summarizes the results for the transportation sector from a larger study, the low carbon study for Brazil, developed by the World Bank as part of its initiative to support the integrated efforts of Brazil to reduce global and national greenhouse gases emissions, while promoting long-term development. The study covers four key areas with potential low carbon options: 1) Land Use, Land Use Change and Forestry (LULUCF), including deforestation, 2) transport systems, 3) production and use of energy, particularly electricity, oil, gas and bio fuels, and 4) municipal waste, solids and liquids. This study aims to underpin Brazil's efforts to explore methods for reducing total emissions of Greenhouse Gases (GHGs) arising from all areas of human activity. More specifically, this study seeks to highlight low-carbon alternatives for Brazil´s transport sector. These alternatives could contribute positively to the world's climate, as well as benefit Brazil's socio-economic development. The technical inputs for evaluating potential carbon emissions reduction will be submitted to the Brazilian government to assist it in the design and deployment of joint planning strategies in key sectors, including transport. To ensure that the study targets the most important areas, it adopts an overarching approach. This means that it made full use of available specialist knowledge (thereby avoiding replication of effort) by undertaking a comprehensive survey of the literature and engaging in a wide-ranging consultation process with recognized Brazilian experts and government technical staff.